Wave loads on ocean infrastructure increase as a result of waves passing over abrupt depth transitions - Li, Z; Tang, T; Li, Y; Draycott, S; Van Den Bremer, T; Adcock, TA (Springer Nature, 2022)
Abrupt changes in water depth are known to lead to abnormal free-surface wave statistics. The present study considers whether this translates into abnormal loads on offshore infrastructure. A fully non-linear numerical model is used which is carefully validated against experiments. The wave kinematics from the numerical model are used as input to a simple wave loading model. We find enhanced overturning moments, an increase of approximately 20%, occur over a distance of a few wavelengths after an abrupt depth transition. We observe similar results for 1:1 and 1:3 slopes. This increase does not occur in linear simulations.